Twenty-four-hour serum creatinine variation is associated with poor outcome in the novel coronavirus disease 2019 (COVID-19) patients - Gaetano Alfano; Annachiara Ferrari; Francesco Fontana; Giacomo Mori; Giulia Ligabue; Silvia Giovanella; Riccardo Magistroni; Marianna Meschiari; Erica Franceschini; Marianna Menozzi; Gianluca Cuomo; Gabriella Orlando; et al. (The Korean Society of Nephrology, 2021)
Background The prognostic value of within-day sCr variation serum creatinine variation is unknown in the setting of the novel coronavirus disease 2019 (COVID-19). We evaluated the prognostic significance of 24-hour serum creatinine variation in COVID-19 patients. Methods A monocentric retrospective analysis was conducted in COVID-19 patients not admitted to the intensive care unit. Three groups were subdivided based on 24 hours serum creatinine variation from admission. In the stable kidney function group, 24-hour serum creatinine variation ranged from +0.05 to -0.05 mg/dL; in the decreased kidney function group, 24-hour serum creatinine variation was >0.05 mg/dL; in the improved kidney function group, 24-hour serum creatinine variation was <-0.05 mg/dL. Results The study population included 224 patients with a median age of 66.5 years and a predominance of males (72.3%). Within 24 hours of admission, renal function remained stable in 37.1% of the subjects, whereas it displayed improved and deteriorated patterns in 45.5% and 17.4%, respectively. Patients with decreased kidney function were older and had more severe COVID-19 symptoms than patients with stable or improved kidney function. About half of patients with decreased kidney function developed an episode of acute kidney injury (AKI) during hospitalization. Decreased kidney function was significantly associated with AKI during hospitalization (hazard ratio [HR], 4.6; 95% confidence interval [CI], 1.9-10.8; p < 0.001) and was an independent risk factor for 30-day in-hospital mortality (HR, 5.5; 95% CI, 1.1-28; p = 0.037). Conclusion COVID-19 patients with decreased kidney function within 24 hours of admission were at high risk of AKI and 30-day in-hospital mortality.